Integrasi Sains dalam Pembelajaran Tauhid Rububiyah dan Pengaruhnya terhadap Pemahaman Konseptual Santri di Pesantren - Faiz Ridhotullah; Imas Masripah (MAN 4 Kota Pekanbaru, 2026)
The dichotomy between religious and scientific knowledge remains a challenge in Islamic boarding school education, particularly in teaching Tauhid Rububiyah, which is often delivered through memorization-based approaches. This study examines the effectiveness of integrating scientific concepts, specifically photosynthesis and metamorphosis, into Tauhid instruction to enhance students’ conceptual understanding. A mixed-method quasi-experimental design with a nonequivalent control group was employed involving 18 students in an Islamic boarding school in Pemalang, Indonesia. Quantitative data were collected through pretest and posttest and analyzed using N-Gain and Welch’s t-test, while qualitative data were obtained through observation and interviews. The results show that the experimental group demonstrated a significant improvement in understanding compared to the control group. The findings indicate that integrating science as empirical manifestations of divine signs enhances cognitive understanding and contextual internalization of theological concepts. This study contributes empirical evidence to the development of integrative models of religious and scientific education in Islamic schooling contexts.